Fun With Pop Up Book : Efektifitas Buku Pop Up Terhadap Peningkatan Perilaku Asertif Anak - Aliyan Syarif Mukhtar; Jeni Fadhila; Faisal Kurnia; Tuti Rahmi; Utari Febriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Assertive is a form of learning that forms the identity of an individual. Assertive ability can also bring up communication skills that can assist individuals in carrying out their social demands. Assertive behavior is important for children to have to prevent sexual violence, bullying and communication difficulties in children. The purpose of this study was to determine the effectiveness of pop up books in increasing assertiveness in children. The method used in this study is an experimental research method which uses a pre-test post-test control group design. Data collection was carried out through observation with the checklist recording technique. Data analysis used is descriptive analysis. The subjects in this study were class II children of SD Negeri Padang Lua for the 2022/2023 academic year, aged 8-9 years. Based on the results of the pre-post test analysis, there was a significant difference in the form of an increase in assertive behavior in the experimental group. This proves that the use of pop up books is effective in increasing assertiveness in children. It is hoped that future researchers will implement this research in a more conducive environment and with a longer intervention time.